2022
DOI: 10.1002/cpe.7467
|View full text |Cite
|
Sign up to set email alerts
|

Generative adversarial network for sentiment‐based stock prediction

Abstract: Financial markets received more attention due to technological advancements, such as Artificial Intelligence (AI). In addition to the price index, traders and investors constantly monitor stock news on social media. Therefore, predicting the market by analyzing public opinions is an important issue. In this research, we propose three models based on Generative Adversarial Network (GAN), namely Price-GAN, Price-Sentiment-GAN, and Price-Sentiment-WGAN. The first model uses only optimized price features, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Liu YL, et al [7] addressed imbalanced text token distribution issues in convolutional neural network sentiment analysis for stock price prediction through a sentiment analysis and GAN-based approach. Furthermore, Sonkiya P, et al [8] proposed an ensemble approach incorporating sentiment analysis and GANs to predict stock prices and Asgarian S, et al [9] introduced three GAN-based models for market trend prediction by analyzing public sentiment. Polamuri SR, et al [10] innovatively applied reinforcement learning and Bayesian optimization, overcoming hyperparameter challenges in a hybrid prediction algorithm based on Generative Adversarial Networks (GAN-HPA).…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu YL, et al [7] addressed imbalanced text token distribution issues in convolutional neural network sentiment analysis for stock price prediction through a sentiment analysis and GAN-based approach. Furthermore, Sonkiya P, et al [8] proposed an ensemble approach incorporating sentiment analysis and GANs to predict stock prices and Asgarian S, et al [9] introduced three GAN-based models for market trend prediction by analyzing public sentiment. Polamuri SR, et al [10] innovatively applied reinforcement learning and Bayesian optimization, overcoming hyperparameter challenges in a hybrid prediction algorithm based on Generative Adversarial Networks (GAN-HPA).…”
Section: Related Researchmentioning
confidence: 99%
“…As articulated in Zhao T, et al [1], nonlinear prediction methods encompass approaches grounded in BP neural networks, support vector machines, recurrent neural networks, generative adversarial networks, and reinforcement learning. Among these, generative adversarial network-based prediction methods [2][3][4][5][6][7][8][9][10], trained through adversarial learning, stand out for their adaptability to the nonlinearity, instability, and complexity of the stock market. They generate data samples aligning more closely with actual market conditions, offering valuable support for stock prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the evolution of AI algorithms and models in financial applications is a key area of interest. Research has shown that AI, particularly deep learning and machine learning, has been extensively utilized for sentiment-based stock prediction and time series data analysis in financial markets (Asgarian et al, 2022;Biju et al, 2023). Furthermore, the integration of AI and quantum computing in finance is an emerging trend that is gaining traction.…”
Section: Future Directions and Trends Of Ai And Quantum Computing In ...mentioning
confidence: 99%